1983
DOI: 10.1007/bf00275950
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of placental glycogen deposition in diabetes in the rat

Abstract: Summary. The metabolic basis for glycogen accumulation in the placenta of rats with diabetes induced by streptozotocin on day 12 of pregnancy was studied on days 15 and 20. On day 15 glycogen content of the placenta was 1.5-fold higher in the diabetic than in the control rats and this difference increased to > fivefold on day 20 of gestation whether calculated per g tissue or per total placenta. Accumulation of glycogen was associated with increased specific activities of both glycogen synthase and phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Glycogen accumulation in the placenta, in face of maternal insulin deficiency and the fact thatbhyperinsulinemia on the fetal side is not more accentuated in diabetic than in control rats, indicates that insulin has no direct influence on glycogen metabolism in this tissue 10 . Glucose flow across the placental is substantially reduced in diabetic hyperglycemia, and there is no convincing demonstration, as yet, of an insulin-dependent, rate-limiting locus in the placenta 20 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Glycogen accumulation in the placenta, in face of maternal insulin deficiency and the fact thatbhyperinsulinemia on the fetal side is not more accentuated in diabetic than in control rats, indicates that insulin has no direct influence on glycogen metabolism in this tissue 10 . Glucose flow across the placental is substantially reduced in diabetic hyperglycemia, and there is no convincing demonstration, as yet, of an insulin-dependent, rate-limiting locus in the placenta 20 .…”
Section: Discussionmentioning
confidence: 98%
“…The placenta is glucose-dependent related with of energy. Maternal glucose transfer by maternal placenta is determined by the glucose concentration and glucose amount stored as glycogen 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, glycogen levels appear to change in a parallel manner. A recent study of placental glycogen synthesis has suggested that the increased formation of this polymer noted in vivo is more clearly reflected by the increased level of substrate present in the tissue (glucose 6-phosphate) than by measurement of the enzymes phosphorylase and glycogen synthese in vitro [30].…”
Section: Discussionmentioning
confidence: 99%
“…Too rapid FFA transfer may produce untoward effects in tissues with fat oxidation capacity not yet fully developed. An analogy may be seen in glucose transport -the pla centa accumulates glycogen proportionately to the level of diabetic hyperglycemia [2,3,5], perhaps as an attempt to moderate the excessive glucose transfer to the fetus. In deed, fetal glucose levels arc at most times no more than two thirds of the maternal ones.…”
Section: Comment and Conclusionmentioning
confidence: 99%